Agenda 21 & the UNCED Proceedings - Robinson, Nicholas A. ed (Oceana Pub. New YorkUS, 1992)
Focuses on those aspects of the United Nations Conference on Environment and Development (UNCED) which are germane to environmental law and the development of environmental norms. Presents documents which help explain the evolution of Agenda 21 and the Declaration of Rio de Janeiro, as important contributions to environmental law.